Parental Dieting and Correlation with Disordered Eating Behaviours in Adolescents: A Narrative Review - Ioanna Kontele; Stella Saripanagiotou; Agni Maria Papadopoulou; Evangelos Zoumbaneas; Tonia Vassilakou (MDPI AG, 2023)
Adolescent eating disorders and disordered eating behaviours appear to be a growing public health concern. The aetiology of these conditions is complex, as many different factors contribute to their development. Among them, family factors such as parenting styles and comments regarding weight coming from family members are considered critical and are extensively researched. However, the impact of parental dieting has received less attention. A literature review was conducted in order to examine the relationship between parental engagement in weight-reduction dieting and their adolescent offspring's disordered eating behaviours. The review was conducted in three databases (PubMed, Scopus and Google Scholar) regarding the period between January 2000 and May 2023. The initial search retrieved 339 abstracts, and 113 full reports were evaluated for eligibility. Six studies fulfilled the inclusion criteria and were included in the final literature review. A number of studies indicated that adolescents whose parents were engaged in dieting in order to lose weight are more likely to showcase disordered eating behaviours. However, research regarding this relationship is very scarce. More studies on the link between parental eating and dieting habits and the risk of disordered eating in adolescents are required. Moreover, parents should be informed regarding the possible risks when they choose to follow weight-loss diets and the importance of adopting healthy eating and weight-control habits for the whole family.